The Effect of Warm Compresses on the Intensity of Labor Pain in Primigravida Mothers in the First Stage of Active Phase at the Blangkajeren City Health Center in 2022 - Mestika Rija Helti; Nila Hayati (Institute of Computer Science (IOCS), 2022)
According to the Ministry of the Republic of Indonesia, from several studies that have been carried out, around 90% of deliveries are accompanied by pain during childbirth. Giving warm compresses is one method to meet the need for comfort and to reduce maternal pain during childbirth. Done by placing a hot jar with a temperature of 42℃on the sacrum area, lower abdomen, and on the perineal area, for 20 minutes. This study aims to analyze the effect of giving warm compresses to reducing pain in in-partu mothers during the active phase I at the Blangkajeren Health Center in 2022. The results of the respondents' pain level before compressing were moderate pain (3.3%), severe pain (43.3%) and very severe pain (53.3%). And the pain level of the respondents after warm compresses was mild pain (16.7%), moderate pain (33.3%), severe pain (26.7%), and very severe pain (23.3%). In conclusion, there is a significant effect of warm compresses on reducing the level of labor pain with the results of the hypothesis test H0 being rejected and Ha being accepted as a significant value of 0.00 <0.05